The occurrence Cryptosporidium Oocysts in selected rivers and its physical assessments in Kuantan, Pahang - Mat Yusof, Afzan; Mohammad, Mardhiah; Abdul Rahman, Muhammad Razman; Abdullah, Qamarul Iqmal; Soffian, Sharmeen Nellisa; Hisamuddin, Nur Hazirah; Hashim, Najat; Abdul Wahab, Ridhwan (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2015)
Cryptosporidium is one of waterborne pathogens causing gastrointestinal illness in humans and animals. In Malaysia, Cryptosporidium related diseases is seemingly neglected and under reported especially at the East Coast region. Therefore, this study was conducted with the aim to provide new information on the occurrence of the Cryptosporidium and its physical assessments in two selected rivers, Balok River and Kuantan River located in Kuantan City, Pahang, Malaysia. Water samples were collected from the downstream of Balok River and Kuantan River for three consecutive months which is known as monsoon season starting from November 2014 until January 2015. The water samples were filtered using flat-bed filtration membrane and immunomagnetic separation methods to detect the presence of Cryptosporidium oocysts. Physical parameters such as dissolved oxygen (DO), pH, temperature and turbidity were measured in situ using hydrolab quanta. The results showed that the occurrence of Cryptosporidium oocysts were higher in Kuantan River than Balok River. We found that the highest occurrence of Cryptosporidium oocysts were in November (0.2 oocysts/L in Balok River and 0.4 oocysts/L in Kuantan River), followed by January (0.2 oocysts/L in both rivers). However, Cryptosporidium was not detected in both Balok River and Kuantan River in December. All the physical parameters were within the range of Interim National Water Quality Standards (INWQS) of Malaysia except for turbidity level in Kuantan River for December 2014 where its turbidity was 355 NTU which was far higher from INWQS range of 50-150 NTU. By using Pearson correlation analysis, it was found that Cryptosporidium oocysts showed significant correlation against dissolved oxygen (DO) (r = -0.96, p < 0.05), pH (r = 0.95, p < 0.05) and turbidity (r = -0.89, p < 0.05) in Balok River. Cryptosporidium oocysts showed significant correlation with DO (r = 0.78, p < 0.05) in Kuantan River. Other parameters showed no significant correlations to the occurrence of Cryptosporidium. These correlation are not consistent in both rivers thus, these parameters are not suitable as indicator for the occurrence of the Cryptosporidium oocysts in Balok River and Kuantan River. Hence, future study on the association of Cryptosporidium from the upstream and midstream of both Balok River and Kuantan River with other parameters such as chemical parameters and heavy metals is needed in order to produce more remarkable findings that can improve water quality monitoring system in Kuantan.